Etika Akuntan Perusahaan dalam Praktik Manajemen Laba Ditinjau dari “Kauffshandlung und Wucher” - Arjuna, Bucek Jalu Prasetyo; Bernawati, Yustrida (E-Jurnal Akuntansi; Vol 30 No 8 (2020)DO - 10.24843/EJA.2020.v30.i08.p08, 2020)
This research was inspired by an article that contained criticism as well as advice in the Middle Ages, kauffshandlung und wucher, written by a Religious Reformer, Martin Luther. Luther's advice consists of four values: being fair, sincere, ready to take risks, and thinking before acting. These values are then brought into earnings management practices because these practices are prone to information manipulation. Using a phenomenology approach, structured interviews were conducted with two Corporate Accountants involved in earnings management practices.  The results of this study show that the four values contained in Luther's advice exist and are applied in Corporate Accountants, especially in earnings management practices, despite the various obstacles faced by Accountants. They continue to strive to meet these values. Keywords: Righteous; Sincere; Take Risks; Thinking Before Acting; Kauffshandlung Und Wucher; Corporate Accountants.